2015
DOI: 10.1007/s40266-014-0230-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multiple Low-Level Anticholinergic Medications on Anticholinergic Load of Community-Dwelling Elderly With and Without Dementia

Abstract: There is considerable scope for the improvement of prescribing practices in the elderly, and particularly those with dementia. Importantly, level 1 anticholinergics have been identified as major contributors to the anticholinergic load in people with dementia. Longitudinal studies are required to determine the effects of increased and decreased anticholinergic load on cognitive function and other clinical outcomes for people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
73
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 52 publications
11
73
2
4
Order By: Relevance
“…Our results mirror community‐based studies that have shown that there is considerable scope for improvement of prescribing practices in older people . Theoretical models have shown that a reduction in anticholinergic burden can be achieved in 59% of patients that score at least one point on the ACB scale and that a reduction from a score of 3 or above to 2 is possible in 85% of the cases .…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Our results mirror community‐based studies that have shown that there is considerable scope for improvement of prescribing practices in older people . Theoretical models have shown that a reduction in anticholinergic burden can be achieved in 59% of patients that score at least one point on the ACB scale and that a reduction from a score of 3 or above to 2 is possible in 85% of the cases .…”
Section: Resultssupporting
confidence: 81%
“…Temporary DAPs were prescribed less in this group compared to patients not on procholinergics on admission (13.5% vs 22.5% of patients, P , .001). This combination of antagonistic drugs makes little sense but is unfortunately frequently encountered . Some of the side effects of dementia drugs, such as urinary frequency, incontinence, diarrhoea or insomnia, may be misinterpreted as new comorbidities or manifestations of frailty in patients with cognitive impairment .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Such symptoms could increase the risk of falls, injuries, fractures, and mortality. Therefore, the use of sedative antidepressants for the NPS of dementia needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Though not recommended, physicians may prescribe a combination of more than one psychotropic drug class in an attempt to manage the NPS, although the evidence base for this practice is even more limited. 21,22 Although the dispensing rates of psychotropics in patients with dementia are well documented in the community setting, 23,24 there are limited reports of their use in the long-term care setting. When compared with dementia patients in the community setting, long-term care patients are older, more frail, and at increased risk of the adverse effects of psychotropic medications; these include potentially dangerous drug interactions between co-dispensed psychotropic medications.…”
mentioning
confidence: 99%